Failure to Meet Nurse Staffing Standards: A Litigation Case Study of a Large US Nursing Home Chain. (19th July 2018) - Harrington, Charlene; Edelman, Toby S.
Large for-profit nursing home chains in the United States have generally reported low nurse staffing levels. This historical case study examined a class action litigation case regarding staffing levels, resident rights, and quality outcomes in 12 Arkansas nursing homes owned by a large for-profit chain. The questions were as follows: (1) How did the residents' care needs compare with actual nurse staffing levels? (2) How did the staffing levels compare with federal and state nurse staffing requirements and professional staffing standards? (3) Did the facilities comply with state and federal residents' rights and quality of care requirements? The findings showed staffing levels marginally above state minimum standards, staffing shortages that violated state standards, staffing levels not adjusted for resident acuity, and shortages that resulted in omitted care. Staffing levels were lower than needed according to nursing directors, lower than average facilities in the state, and lower than professional standards. The findings showed many resident grievances regarding basic care and residents' rights, clinical measures of poor quality, and state deficiencies. A large settlement was agreed on to compensate the residents. The case shows that chain's management, as well as the regulatory system, failed to ensure adequate staffing levels that took into account regulatory requirements and professional standards and resulted in violations of residents' rights, health, safety, and well-being.